Overweight/obesity in adolescents with phenylketonuria: protective and predisposing factors - Adriana Márcia Silveira; Poliane Lopes Lima; Michelle Rosa Andrade Alves; Rosângelis Del Lama Soares; Viviane de Cássia Kanufre; Valéria de Melo Rodrigues; Ana Lúcia Pimenta Starling; Rocksane de Carvalho Norton; Marcos José Burle de Aguiar (Elsevier, 2022)
Objective: To estimate the prevalence and factors associated with overweight/obesity development in adolescents with early diagnosed phenylketonuria treated exclusively by diet. Methodology: In this cross-sectional study anthropometric measurements, serum phenylalanine levels, and 10 metabolites associated with lipid and carbohydrate metabolism were analyzed in 101 adolescents aged 10-20 years. Adolescents were categorized into overweight/obesity and eutrophic/low body mass index groups. These patients were compared using Student's t-test, Pearson's chi-square test, Wald's chi-square test for multivariate analysis. Further, to verify whether the prevalence of overweight/obesity found in the study population was similar to that in the general population, the authors compared the nutritional status of 46 patients aged 13-17 years with that of healthy students of the same age from the National School Health Survey using the chi-square test for adherence. The significance threshold was p < 0.5. Results: The prevalence of overweight/obesity in adolescents was 27.7%. There was no difference in prevalence between sexes. Older age was a protective factor and Increased Homeostasis Model Assessment Insulin Resistance index and high phenylalanine and low-density lipoprotein cholesterol levels were predictive factors for overweight/obesity. The equality hypothesis was not rejected in the comparison of nutritional states of 46 patients aged 13-17 years and healthy students of the same age. Conclusion: The prevalence of overweight/obesity in phenylketonuria adolescents was similar to what is found in healthy adolescents.